MEWAKILKAN KABUL NIKAH KEPADA ORANG LAIN DALAM PELAKSANAAN PERNIKAHAN - Muallim Hasibuan (AL-ILMU, 2022)
Marriage is the deepest, strongest and eternal bond that connects two human children of different sexes. Therefore there must be a unity of heart, must meet in a bond that is not easily separated. If a Muslim is determined to get married and directs his intention to propose to a certain woman, then it is recommended to see the woman before starting his steps to the marriage ladder, so that he can face his marriage clearly and not be deceived. The scholars of the school agree that a new marriage is considered valid if it is carried out with a contract that includes consent and qabul between the proposed woman and the man who proposed to her, and is considered invalid based solely on consensual consent without a contract. The scholars of the school also agree that marriage is valid if it is carried out using the editor of jawwaztu (I marry) or I marry from the proposed party or the person who represents him and the editor of qobiltu (I accept) or radhitu (I agree) from the party who proposes or represents him .Representation is allowed in the contract, so the groom can represent whom he wants and the bride's guardian who holds the marriage contract. In the Compilation of Islamic Law Article 29 paragraph 1 it is stated that those who have the right to say Kabul are the prospective groom personally. In certain cases, the marriage acceptance speech can be represented to another man provided that the prospective groom gives explicit authorization in writing that the acceptance of the representative for the marriage contract is for the groom, but this permission can only be exercised if the prospective bride or guardian does not object. if the groom-to-be is represented. If a person who is going to perform the marriage contract cannot attend, but he still wants to do it, then that person is required to send a messenger or write a letter to a second party to explain that he still wants to perform the contract. If the second party agrees to carry out the contract, then he is required to bring in a number of witnesses (at least two men or one man and two women).